Femoral tunnel placement: Antero-medial versus Trans-Tibial for Anterior Cruciate Ligament Reconstruction by using Peroneus Longus Graft - Munir, Shahid; Maqbool, Wajahat; Rafique, Hammad; Cheema, Ali Raza; Wattoo, Shehryar; Malik, Ahmed Tariq (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare Antero-medial versus Trans-Tibial femoral tunnel placement for anterior cruciate ligament reconstruction by using peroneus longus graft. Study Design: Prospective comparative study. Place and Duration of Study: Orthopedic Department, Combined Military Hospital, Lahore Pakistan, from Jul 2020 to Jun 2023. Methodology: We included all the young patients who underwent anterior cruciate ligament reconstruction via peroneus longus graft. Patients were randomly divided into two groups for comparison. One group had femoral tunnel placement via antero-tibial drilling while other had via trans-tibial route. Both the groups were followed up for three months for comparison of stability, achievement of anatomical position, pain score and muscle strength. Results: A total of 125 patients who had ACL reconstruction surgery were recruited in this study. Mean age of these patients was 28.25±6.81 years. Out of the total study participants, 108(86.4%) were military personals while 17(13.6%) patients were civilian-non entitled. Out of 125 patients, 64(51.2%) had femoral tunnel placement via anteromedial route while 61(48.8%) had via transtibial route. Statistical analysis revealed that at the end of three months’ patients in both groups had no statistically significant difference in stability of joint, achievement of anatomical position on x-ray, significant pain and muscle strength (p-value >0.05). Conclusion: Both the methods used for femoral tunnel placement for reconstruction of anterior cruciate ligament by using peroneus longus graft were equally efficacious in terms of stability, achievement of anatomical position, pain score and muscle strength.